Cardiometabolic Center of Excellence: A Novel Care Delivery Model for Secondary Prevention of Cardiovascular Disease in Type 2 Diabetes. Issue 10 (30th September 2021) - Thomas, Merrill; Magwire, Melissa; Gosch, Kensey; Sammour, Yasser; Mehta, Rane; O'Keefe, James; Nassif, Michael E.; Kosiborod, Mikhail
Abstract : Supplemental Digital Content is available in the text.